Scattered finds : archaeology, egyptology and museums - Stevenson, Alice (UCL Press, 2019)
By juxtaposing a diversity of sites for the reception of Egyptian cultural heritage over the period of a century, this book presents new ideas about the development of archaeology, museums and the construction of Egyptian heritage. It also addresses the legacy of these practices and argues for a stronger ethical commitment to its stewardship.